2015
DOI: 10.1186/s12961-015-0068-x
|View full text |Cite
|
Sign up to set email alerts
|

The NIHR Public Health Research Programme: responding to local authority research needs in the United Kingdom

Abstract: The remit of the National Institute for Health Research Public Health Research (PHR) Programme is to evaluate public health interventions, providing new knowledge on the benefits, costs, acceptability and wider impacts of interventions, set outside of the National Health Service, intended to improve the health of the public and reduce inequalities. This paper illustrates how the PHR Programme is providing new knowledge for public health decision makers, based on the nine key areas for local authority public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In 2019/20 the total public health grant for local authorities was £3.13 billion [ 3 ] but this grant has been significantly cut by £200 million in recent years [ 4 ]. Continuous cuts to public services pose significant challenges for local authorities, increasing the need for reliable and timely evidence to optimise the use of resources to improve population health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019/20 the total public health grant for local authorities was £3.13 billion [ 3 ] but this grant has been significantly cut by £200 million in recent years [ 4 ]. Continuous cuts to public services pose significant challenges for local authorities, increasing the need for reliable and timely evidence to optimise the use of resources to improve population health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that across the board, the public health research community was involved in generating ideas, but other groups of potential stakeholders had lesser involvement. The NIHR PHRP’s inclusion of public health decision-makers in both its stakeholder events and its decision-making committee is noteworthy in this regard, and a recent article found that the priority-driven research funded by the NIHR PHRP matched the areas that national guidelines recommended local authorities act on to improve population health [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Public Health Innovation and Research in Europe project represents perhaps the most in-depth research on European public health research funders [ 2 ]. Additional studies have focused on the research funding priorities of individual funding organisations, like the National Institutes for Health Research (NIHR) [ 3 , 4 ], the National Health and Medical Research Council (NHMRC) [ 5 ] and the United States National Institutes for Health [ 6 ]. Given that priority funding areas are identified and refreshed more or less frequently, the published literature, while historically interesting, does not offer insight into the current priority-driven funding trends.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, an examination of ethics approval systems in various countries, which was generally positive about reforms in the system in England [10]; an account of how the NIHR has responded to the research needs of local government in the United Kingdom after responsibility for public health was transferred to it [11]; and an analysis of how an NIHR initiative to integrate research into the local healthcare system was successfully implemented in North West London [12]. …”
Section: Editorialmentioning
confidence: 99%